2004
DOI: 10.1086/383321
|View full text |Cite
|
Sign up to set email alerts
|

Miltefosine for New World Cutaneous Leishmaniasis

Abstract: The oral agent miltefosine has demonstrated a >95% cure rate in Indian visceral leishmaniasis. We performed a large, placebo-controlled study of miltefosine therapy (2.5 mg/kg per day orally for 28 days) against cutaneous leishmaniasis in Colombia and Guatemala. In regions in Colombia where Leishmania vianna panamensis is common, the per-protocol cure rates for miltefosine and placebo were 91% (40 of 44 patients) and 38% (9 of 24). These values are similar to historic values for the antimony standard of care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
216
1
16

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(244 citation statements)
references
References 29 publications
(24 reference statements)
5
216
1
16
Order By: Relevance
“…The differences in therapeutic response in the previous study in Colombia and Guatemala were attributed to the species of Leishmania predominant in each country 22 . The data for Colombia, however, was mainly based on historical records, given that only seven isolated strains were identified in the study from the 73 study participants, and all were identified as L. (V.) panamensis.…”
Section: Discussionmentioning
confidence: 65%
“…The differences in therapeutic response in the previous study in Colombia and Guatemala were attributed to the species of Leishmania predominant in each country 22 . The data for Colombia, however, was mainly based on historical records, given that only seven isolated strains were identified in the study from the 73 study participants, and all were identified as L. (V.) panamensis.…”
Section: Discussionmentioning
confidence: 65%
“…Miltefosine was effective in curing patients with visceral leishmaniasis in India; however, few studies on the treatment of tegumentary leishmaniasis have been reported. In Colombia, a cure rate of 89-100% was observed for cutaneous leishmaniasis and was dependent on the dose used [86]; however, in general, the results in the New World are poor [87].…”
Section: Alternative Drugsmentioning
confidence: 99%
“…without conclusive results (DOGRA & SAXENA, 1996;ALRAJHI et al, 2002). Recently, patients with cutaneous leishmaniasis caused by L. (Viannia) panamensis in Colombia received miltefosine and presented cure rate of 91%, whereas, in Guatemala, only 50% of cure was obtained in patients infected by L. (Viannia) brasiliensis (SOTO et al, 2004). The results in patients with visceral leishmaniasis in India also showed good efficacy (93%) with this drug (SUNDAR et al, 2002).…”
Section: Introductionmentioning
confidence: 99%